Expansion of Public Law into the Sphere of Private Interests: Strengthening State Regulation as a New Management Paradigm - USANOV, Vladimir E. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).38, 2020)
Relevance. The article is relevant since the recent events have revealed the illusory nature of democratic principles and the independence of private interests in the Russian Federation. The illusion of free choice and democratic procedures disappeared when public authorities declared a state of emergency or self-isolation regime (quarantine during the COVID-2019 pandemic) facing a force that exceeded the resources and capabilities of the government systems. Objective . The article aims at studying a new global model of expanding public law into the sphere of private interests due to strengthening the state regulation of public relations as a new management paradigm. The current model typical of many countries, in particular Russia, can be called a model of an actual emergency. The Russian Federation did not declare de jure state of emergency. Otherwise, public authorities would have to take on big obligations and be responsible for losses (damages, contract failures, suspended trading and production, downsizing, unemployment) of their citizens and businesses. Methods . The main research method was deduction used for studying the legal specifics of expanding public law into the sphere of private interests. The author of the article also used the inductive, comparative-legal and historical methods, as well as the method of systematic scientific analysis. To solve the task, it is necessary to consider the legal foundations and features of strengthening state regulation as a new management paradigm. Results. Analyzing the actual state of emergency experienced by most countries and considering the actions of the Russian authorities, the author claims that public law serves as the basis of public administration but invades the sphere of private interests. It begins to manage it in a state of emergency to preserve the existing state system and its integrity. As a result, private law ceases to be independent and must obey the rules of public law. At the same time, the democratic traditions and principles proclaimed in the Constitution and other laws, human rights and civil freedoms are instantly absorbed by public law and become a legal fiction for a certain time.